West Wingers : stories from the dream chasers, change makers, and hope creators inside the Obama White House - Raghavan, Gautam (Penguin Books, An imprint of Penguin Random House LLC, 2018)
"The Obama White House staff invites us behind-the-scenes of history for a deeply personal and moving look at the presidency and how a president's staff can change the nation"--